Steam gasification of rapeseed, wood, sewage sludge and miscanthus biochars for the production of a hydrogen-rich syngas - Sattar, Anwar; Leeke, Gary A.; Hornung, Andreas; Wood, Joseph (Elsevier, 2014)
Steam gasification of biochars has emerged as a promising method for generating syngas that is rich in hydrogen. In this study four biochars formed via intermediate pyrolysis (wood pellet, sewage sludge, rapeseed and miscanthus) were gasified in a quartz tubular reactor using steam. The dynamic behaviour of the process and effects of temperature, steam flow and particle size were studied. The results show that increases in both steam flow and temperature significantly increase the dry gas yield and carbon conversion, but hydrogen volume fraction decreases at higher temperatures whilst particle size has little effect on gaseous composition. The highest volume fraction of hydrogen, 58.7%, was obtained at 750 °C from the rapeseed biochar.
Keywords: Biochar steam gasification; Intermediate pyrolysis; Brassica napus; Sewage sludge; Miscanthus x giganteus; Pinus sylvestris – Picea sitchensis